Extraction techniques for bioactive compounds of cannabis. Issue 3 (10th January 2023) - Sainz Martinez, Aitor; Lanaridi, Olga; Stagel, Kristof; Halbwirth, Heidi; Schnürch, Michael; Bica-Schröder, Katharina
Abstract : The beneficial properties of bioactive compounds of cannabis has renewed the scientific interest in their recovery. This review presents the available extraction techniques for these valuable compounds, along with a discussion on reporting practices. Abstract : Historically, cannabis has always constituted a component of the civilized world; archaeological discoveries indicate that it is one of the oldest crops, while, up until the 19th century, cannabis fibers were extensively used in a variety of applications, and its seeds comprised a part of human and livestock nutrition. Additional evidence supports its exploitation for medicinal purposes in the ancient world. The cultivation of cannabis gradually declined as hemp fibers gave way to synthetic fibers, while the intoxicating ability of THC eventually overshadowed the extensive potential of cannabis. Nevertheless, the proven value of certain non-intoxicating cannabinoids, such as CBD and CBN, has recently given rise to an entire market which promotes cannabis-based products. An increase in the research for recovery and exploitation of beneficial cannabinoids has also been observed, with more than 10 000 peer-reviewed research articles published annually. In the present review, a brief overview of the history of cannabis is given. A look into the classification approaches of cannabis plants/species as well as the associated nomenclature is provided, followed by a description of their chemical characteristics and their medically valuable components. The application areas could not be absent from the present review. Still, the main focus of the review is the discussion of work conducted in the field of extraction of valuable bioactive compounds from cannabis. We conclude with a summary of the current status and outlook on the topics that future research should address.